Second and third trimester fetal ultrasound population screening for risks of preterm birth and small-size and large-size for gestational age at birth: a population-based prospective cohort study: Fetal ultrasound screening for common adverse birth outcomes - Erkamp, Jan S. (BMC Med, 2020)
BACKGROUND: Preterm birth, small size for gestational age (SGA) and large size for gestational age (LGA) at birth are major risk factors for neonatal and long-term morbidity and mortality. It is unclear which periods of pregnancy are optimal for ultrasound screening to identify fetuses at risk of preterm birth, SGA or LGA at birth. We aimed to examine whether single or combined second and third trimester ultrasound in addition to maternal characteristics at the start of pregnancy are optimal to detect fetuses at risk for preterm birth, SGA and LGA. METHODS: In a prospective population-based cohort among 7677 pregnant women, we measured second and third trimester estimated fetal weight (EFW), and uterine artery pulsatility and umbilical artery resistance indices as placenta flow measures. Screen positive was considered as EFW or placenta flow measure < 10th or > 90th percentile. Information about maternal age, body mass index, ethnicity, parity, smoking, fetal sex and birth outcomes was available from questionnaires and medical records. Screening performance was assessed via receiver operating characteristic (ROC) curves and area under the curve (AUC) along with sensitivity at different false-positive rates. RESULTS: Maternal characteristics only and in combination with second trimester EFW had a moderate performance for screening for each adverse birth outcome. Screening performance improved by adding third trimester EFW to the maternal characteristics (AUCs for preterm birth 0.64 (95%CI 0.61 to 0.67); SGA 0.79 (95%CI 0.78 to 0.81); LGA 0.76 (95%CI 0.75; 0.78)). Adding third trimester placenta measures to this model improved only screening for risk of preterm birth (AUC 0.72 (95%CI 0.66 to 0.77) with sensitivity 37% at specificity 90%) and SGA (AUC 0.83 (95%CI 0.81 to 0.86) with sensitivity 55% at specificity 90%). Combining second and third trimester fetal and placental ultrasound did not lead to a better performance as compared to using only third trimester results. CONCLUSIONS: Combining single third trimester fetal and placental ultrasound results with maternal characteristics has the best screening performance for risks of preterm birth, SGA and LGA. As compared to second trimester screening, third trimester screening may double the detection of fetuses at risk of common adverse birth outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12916-020-01540-x) contains supplementary material, which is available to authorized users.